Polyploid Evolution of the Brassicaceae during the Cenozoic Era . Issue 7 (17th July 2014) - Kagale, Sateesh; Robinson, Stephen J.; Nixon, John; Xiao, Rong; Huebert, Terry; Condie, Janet; Kessler, Dallas; Clarke, Wayne E.; Edger, Patrick P.; Links, Matthew G.; Sharpe, Andrew G.; Parkin, Isobel A.P.
Abstract : This study identified multiple whole-genome duplication (WGD) events among Brassicaceae species. Remarkably, these events, as well as previously identified WGD events, are synchronized in age, coincident with epoch transitions, adding to the evidence suggesting the environmental instability associated with these transitions favors polyploidy and rapid species diversification. Abstract: The Brassicaceae (Cruciferae) family, owing to its remarkable species, genetic, and physiological diversity as well as its significant economic potential, has become a model for polyploidy and evolutionary studies. Utilizing extensive transcriptome pyrosequencing of diverse taxa, we established a resolved phylogeny of a subset of crucifer species. We elucidated the frequency, age, and phylogenetic position of polyploidy and lineage separation events that have marked the evolutionary history of the Brassicaceae. Besides the well-known ancient α (47 million years ago [Mya ]) and β (124 Mya ) paleopolyploidy events, several species were shown to have undergone a further more recent (∼7 to 12 Mya ) round of genome multiplication. We identified eight whole-genome duplications corresponding to at least five independent neo/mesopolyploidy events. Although the Brassicaceae family evolved from other eudicots at the beginning of the Cenozoic era of the Earth (60 Mya ), major diversification occurred only during the Neogene period (0 to 23 Mya ). Remarkably, the widespread species divergence, major polyploidy, and lineage separation events during Brassicaceae evolution are clustered in time around epoch transitions characterized by prolonged unstable climatic conditions. The synchronized diversification of Brassicaceae species suggests that polyploid events may have conferred higher adaptability and increased tolerance toward the drastically changing global environment, thus facilitating species radiation.